Racial and gender differences in the incidence of recurrent venous thromboembolism - White, Richard H.; Dager, William E.; Zhou, Hong; Murin, Susan (Thrombosis and Haemostasis, 2006)
Men have been reported to have a higher incidence of recurrent venous thromboembolism than women. However, it is not known if this gender effect holds among different racial/ethnic groups and for both venous thrombosis and pulmonary embolism. We conducteda retrospective analysis of 18-to 65-year-old Caucasian, African-American and Hispanic cases hospitalized in California with unprovoked venous thromboembolism. The principal outcome was recurrent venous thromboembolism 7–60 months after the index event. Among 11,514 cases that were followed for a mean of 3.0 years, men had a significantly higher rate (events/100 patient-years) of recurrent venous thromboembolism than women for both venous thrombosis [rate ratio (RR)=1.5, 95% confidence interval (CI):1.3–1.8] and pulmonary embolism [RR=1.3, 95%CI:1.0–1.6].Among men the recurrence rate did not vary significantly between the racial/ethnic groups (p>0.05). However, the recurrence rate among Hispanic women with venous thrombosis was significantly higher than in Caucasian women (p<0.001) and was comparable to the rate in men. Both Hispanic and African-American women with pulmonary embolism had a higher recurrence rate compared with Caucasian women (p<0.02) that was comparable to the rate in men. We conclude that women in California had a 40% lower risk of recurrent venous thromboembolism compared to men. Rates were comparable among men of different races, but there were significant inter-racial differences among women, which also varied with the type of initial event. The effect of gender on the risk of recurrent venous thromboembolism can not be generalized because it varies between racial/ethnic groups and with the type of index event.
Keywords: Race; ethnicity; gender; recurrent thromboembolism; epidemiology